Soil compaction and wetness effects on efflux of greenhouse gases - AISHWATH, O. P.; LAL, R. (Journal of Soil and Water Conservation, 2020)
Excessive soil compaction exacerbates physical, chemical and biological processes which influenceaeration, emission of greenhouse gases (GHG) and other agricultural and environmental implications.An incubation involving bulk density (Ïb) in the range of 1.2-1.8 Mg m-3 and field moisture capacity (FC)of 100%, 50% and 25% for 4 week. The results indicated that emissions of CO2, CH4 and N2O were thehighest on 7th day and reduced thereafter. However, N2O flux at Ïb of 1.4 Mg m-3 and CH4 at Ïb 1.6 Mgm-3 and 1.8 Mg m-3 increased with duration of incubation. The flux of CO2 was always higher at moderatecompaction (Ïb 1.4 Mg m-3) and moisture (FC-50%). In general, CO2 flux was more affected by soil moisturecontent than by compaction. However, CH4 flux was more with higher compaction and moisture whichincreased sharply on the 7th day and remained constant up to 21 days. Flux of N2O was the highest at Ïbof 1.8 Mg m-3 and 25% of FC. Irrespective of Ïb and moisture regimes, N2O flux increased sharply on the7th day and remained constant up to 28th day. The fluxes of N2O and CO2 were negatively correlated withsoil moisture content and Ïb. However, flux of CH4 was positively correlated with soil moisture and Ïb.